Recombinant Enzyme: Cloning and Expression - Amid, Azura; Hassan, Norhidayah (Springer International Publishing, 2015)
This chapter will discuss the general strategies of cloning recombinant enzymes from identifying a suitable DNA template to choosing the correct host expression system. However, there is no standard operating procedure for cloning a recombinant enzyme. The best strategies should be based on the researcher’s creativity and experiences.